Memory and identity personal reflections - John Paul II, Pope. (London Hachette, 2005)
A truly historical document, Memory and Identity contains Pope John Paul II's personal thoughts on some of the most challenging issues and events of his turbulent times. Pope for over 26 years, he was one of the world's greatest communicators and this moving book provides a unique insight into his intellectual and spiritual journey and pastoral experience.
Includes index
Keywords: John Paul II, Pope, 1920-2005--Interviews.